Audit Committee Characteristics and Sustainability Practices Disclosure: Empirical Evidence of Islamic Banks in Indonesia - Erlinda Nur Khasanah (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aimed to examine the characteristics of audit committee on sustainability practices disclosure and to explore the extent to which Indonesian Islamic Banks disclosed their sustainability practice in annual report. The research method used in this study was quantitative method. The objects of this study were annual report of Indonesian Islamic Banks from 2013-2018. Total sample consisted of 66 samples. To test the hypothesis, this study used multiple regression test by using SPSS 21 program. This result showed that Indonesian Islamic Banks have quite low of sustainability practices disclosure rating. This study found that the size of audit committee and the composition of an independent audit committee significantly influenced the sustainability practices disclosure. This study also provided empirical evidence that the frequency of audit committee meetings, the audit committee’s qualification and the audit committee’s experience was not significant on sustainability practices disclosure.